Students’ Perspective in Creating Comic Strip Recount Text by Using Canva: A Survey Study - Fitri Ulya Dewi; Maria Yosephine Widarti Lestari; Theresia Cicik Shopia Budiman; Rossana Rossana (Universitas PGRI Semarang, 2023)
. In the 21st century the implementation of Technological Pedagogical Content Knowledge (TPACK) is a fundamental aspect in English Language Teaching (ELT). Canva is one of alternative free application that can be used by both students and teachers in English learning process. This study aimed to find out studentsâ€™ perspective in creating comic strip of recount text by using Canva. This study applied descriptive qualitative method. The subject of this study is eighth-B grade students of SMP Negeri 36 Semarang. The participants were given a questionnaire consisted of two indicators namely perceived excitement and perceived easy to use and usefulness. The first indicator concluded students happy in using Canva, learning recount text by creating comic strip in Canva is interesting, students motivated to study more about recount text when using Canva, the images, font, colours in Canva are very attractive, and students exited to use Canva outside of learning process. Then, the second indicator concluded that students can use Canva, creating comic strip ofÂ recount text by using Canva is easy, the comic strip template on Canva helps students to create products in learning recount text, Canva is one of the best alternative in learning application and they want to explore Canva more. Moreover to explore the detailed perspective, the researchers held interview. The data interview showed there are several reasons why they are happy in using Canva. It because this application can be accessed for free. They can also download and used it easily in their smartphone.